2022
DOI: 10.1055/a-1880-1264
|View full text |Cite
|
Sign up to set email alerts
|

Early Clinical, Biochemical and Radiological Features in Obese and Non-Obese Young Women with Polycystic Ovarian Syndrome: A Comparative Study

Abstract: Polycystic ovarian syndrome (PCOS) is a heterogenous condition accounting for serious health complications. The present study was conducted to assess the early clinical, biochemical, and radiological features in obese, non-obese young women with PCOS as compared to non-PCOS women. The study was conducted on 120 young women (18–22 years) with 80 having features of PCOS [40 obese (BMI≥25 kg/m2) and 40 non-obese … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…On the contrary, Ray [113] has reported that obesity is positively associated with PCOS individuals in the rural population. Waist circumference and clinical indicators of hyperandrogenism should be taken into account while developing effective treatment plans [33,77,103].…”
Section: Obesitymentioning
confidence: 99%
“…On the contrary, Ray [113] has reported that obesity is positively associated with PCOS individuals in the rural population. Waist circumference and clinical indicators of hyperandrogenism should be taken into account while developing effective treatment plans [33,77,103].…”
Section: Obesitymentioning
confidence: 99%
“…Although it is still unknown whether IR is a cause or effect of PCOS, the strong connection between AN and PCOS is based on the mechanisms of IR and hyperinsulinemia, which could also explain elevated levels of free testosterone in the PCOS population. Although it is a well-known fact that AN is associated with obesity and IR, there are limited data regarding normal-weighted people with PCOS [ 126 , 127 , 128 , 129 , 130 , 131 , 132 ]. As expected, AN was more frequent among obese women with PCOS versus normal-weighted women with PCOS; however, obesity itself is recognized as an independent risk factor for IR, irrespective of PCOS [ 126 ].…”
Section: An and Pcosmentioning
confidence: 99%
“…Although it is a well-known fact that AN is associated with obesity and IR, there are limited data regarding normal-weighted people with PCOS [ 126 , 127 , 128 , 129 , 130 , 131 , 132 ]. As expected, AN was more frequent among obese women with PCOS versus normal-weighted women with PCOS; however, obesity itself is recognized as an independent risk factor for IR, irrespective of PCOS [ 126 ].…”
Section: An and Pcosmentioning
confidence: 99%
“…Secondary supporting laboratory findings consistent with PCOS include: 1) a markedly elevated anti-müllerian hormone (AMH) level, 12 2) an elevated fasting insulin level, 2,13 and 3) an elevated luteinizing hormone (LH) to follicle-stimulating hormone (FSH) ratio. 13,14 But it is not necessary to measure AMH, fasting insulin, LH, and FSH levels. To conserve health care resources, I recommend against measuring those analytes to diagnose PCOS.…”
Section: Simplify the Diagnosis Of Pcosmentioning
confidence: 99%